2020
DOI: 10.1021/acs.langmuir.0c02719
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Insights into Adhesion at a Buried Silica-Filled Silicone/Polyethylene Terephthalate Interface

Abstract: Silicone adhesives are widely used in many important applications in aviation, automotive, construction, and electronics industries. The mixture of (3glycidoxypropyl)trimethoxysilane (γ-GPS) and hydroxy-terminated dimethyl methylvinyl co-siloxanol (DMMVS) has been widely used as an adhesion promoter in silicone elastomers to enhance the adhesion between silicone and other materials including polymers. The interfacial molecular structures of silicone elastomers and the adhesion promotion mechanisms of a γ-GPS-D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
60
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 28 publications
(61 citation statements)
references
References 70 publications
1
60
0
Order By: Relevance
“…A picosecond SFG system was used for experiments in this study (EKSPLA, Lithuania, model PL2231-20-RS232). SFG vibrational spectroscopy was extensively used to probe the surfaces and interfaces of the materials due to its intrinsic surface sensitivity. SFG theories, setups, and instrumentation will thus not be stated in detail. Briefly, two input beams, a visible beam with a fixed wavelength at 532 nm and a frequency-tunable infrared (IR) beam, were overlapped spatially and temporally on the surfaces of the samples.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A picosecond SFG system was used for experiments in this study (EKSPLA, Lithuania, model PL2231-20-RS232). SFG vibrational spectroscopy was extensively used to probe the surfaces and interfaces of the materials due to its intrinsic surface sensitivity. SFG theories, setups, and instrumentation will thus not be stated in detail. Briefly, two input beams, a visible beam with a fixed wavelength at 532 nm and a frequency-tunable infrared (IR) beam, were overlapped spatially and temporally on the surfaces of the samples.…”
Section: Methodsmentioning
confidence: 99%
“…Sum frequency generation (SFG) vibrational spectroscopy has been demonstrated to be a suitable tool to understand the change of molecular structures of surfaces and interfaces. SFG enables precisely measuring the molecular structure/behavior of surfaces/interfaces by its surface/interface-sensitive nature. SFG has been extensively applied to study the surface and interfacial molecular structures of polymers, including various polymer adhesives. , In this study, the atmospheric moisture effect on the surfaces of isocyanate-based primers was probed by SFG, and the molecular behaviors of such surfaces were correlated to the macroscopic properties to investigate the relationship. Different conditions in the experiments were set up in a variation of humidity levels and exposure time to understand the influences of their effects on the primer surfaces.…”
Section: Introductionmentioning
confidence: 99%
“…In previous work, we have examined the molecular interactions between poly(ethylene terephthalate) (PET) and silicone with silane adhesion promoters, and successfully detected interfacial reactions involving methoxy and epoxy groups. 48 To the best of our knowledge, the interfacial chemical reactions between nylon and silane-containing silicone have not been examined and the related molecular adhesion promotion mechanisms are not yet well understood. Here, we studied two silicone adhesives, both containing trialkoxysilane coupling agents, but with different organofunctional groups.…”
Section: Introductionmentioning
confidence: 99%
“…There is a need to develop an ultrasensitive technique which could be used to study the distribution of ultrathin silicone oil layers on surfaces. In recent decades, second-order nonlinear optical spectroscopic techniques such as sum frequency generation (SFG) vibrational spectroscopy and second-harmonic generation (SHG) have been applied to study molecules (including proteins) on surfaces and at interfaces. Such research demonstrated that second-order nonlinear optical spectroscopic techniques are very promising in detecting monolayer and even submonolayer molecules at interfaces in situ. SFG has been applied to examine the molecular structures of surfaces and interfaces involving solid silicone and silicone oil to understand important interfacial properties such as adhesion, friction, antifouling, and fouling release. In particular, SFG has been applied to study thin films of silicone on water surfaces . SFG provides chemical and orientational information on the molecular structure of chemical groups at interfaces.…”
Section: Introductionmentioning
confidence: 99%